Case study of safety status of laboratory workers in a chemical industrial plant - Kreunin, Paweena; Paibulpanich, Akarin; Paibulpanich, Akarin; Buthkhunthong, Pitchaya; Paibulpanich, Akarin (Bulletin of Applied Sciences, 2022)
This case study quantitatively examines the safety status of laboratory staff of a private chemical factory, by focusing on the aspects of safety training, practices, and safety management system. Questionnaires are used as a data collection tool. The opinions of 205 staffs are collected. The statistical analysis used is frequency, percentage, and average using Microsoft Excel. The results showed that the majority of laboratory personnel have been trained on safety before working in the laboratories and the safety knowledge is gained from both within and outside the organization. There is also an exchange of knowledge between staff in the agency. In addition, the workers have put knowledge of using Personal Protective Equipment (PPE) and Safety Data Sheet (SDS) into practice, and most of them agree that the organization has a good safety management system. Even though the majority of laboratory personnel have been trained on safety and the organization has a good safety management system, chemical accidents did occur and there were cases of being admitted to hospital or medical facility. These facts show that the organization's safety system still needs further improvement. For example, the staffs of laboratory agree that the organization must have knowledge refresher trainings, continuously promote in-depth understanding on safety issues. Also the organization should promote cultural awareness on chemical operations, regular conduct risk assessments, and improve guidelines to achieve true safety. This case study can be used as an example for other agencies to conduct surveys in a similar manner to improve and promote safety at work